Analysis and Comparison of SMAC and TMAC Protocol for Energy Efficient Dynamic Topology in Sensor Network - Tapaswini Samant; Amlan Datta (Institute of Advanced Engineering and Science, 2016)
In the era of wireless communication, wireless sensor is one of the best technologies we are witnessing. In case of environmental monitoring, tactical systems and different tracking applications, wireless sensors are being used. Here, the corresponding nodes operate on incomplete power and thus the energy comes into play to operate these entire networks. Managing the energy and its utilization is vital for TCP/IP protocol suite which is MAC layer’s application. Thus keeping in mind the above challenges, the techniques used are increasing the sleep duration, over hearing and ideal listening, collision of packet and eliminating hidden terminal problem. This paper is oriented towards the comparison of energy consumption by SMAC and TMAC protocol. The characteristics of TMAC and SMAC protocols were explored keeping real transmission conditions intact, like variable transmission bit rate, dynamic topology and mobile sensors in network. TMAC and SMAC protocols are contention based protocols and are designed to keep the energy consumption low using duty cycle.